ANALISIS PENDAPATAN USAHATANI KANGKUNG (Ipomoea reptans poir) JALAN SUKAMARA KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANG ANGGANG KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Wasdiyanta Wasdiyanta (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
This research takes the title of the analysis of kangkung farming income (ipomeae reptans poir)The observation was carried out on Sukamara Street in March 2020 with a simple random sampling method.This research was conducted by survey method with participatory observation techniques, the purpose of this research is to find out how to cultivate water spinach farming and how much is the total cost and income in one growing season the results of the study obtained a total cost of Rp. 34,570,305, -, receipt of Rp. 67,554,000, - so the income is Rp. 32,983,685